2014
DOI: 10.3402/dfa.v5.22936
|View full text |Cite
|
Sign up to set email alerts
|

A study of prognostic factors in Chinese patients with diabetic foot ulcers

Abstract: ObjectiveFew studies have identified factors as predictors of clinical prognosis of patients with diabetic foot ulcers (DFUs), especially of Chinese patients. In this study, we assessed the prognostic factors of Chinese patients with DFUs.Methods and materialsThis was a retrospective study (January 2009–January 2011) of 194 DFUs conducted in an inpatient population at PLA 454 Hospital in Nanjing, China, to determine the prognostic influential factors of DFUs in Chinese patients. All of the studied patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 17 publications
1
40
0
1
Order By: Relevance
“…Wang 21 also found that an abnormal ABI was more prevalent in patients with non-healing ulcers. High risk was also more prevalent among diabetics with reduced palpability of lower limb pulses (14.04%); correlating with Margolis, in whose study of diabetic foot patients, 20% had distal vasculopathy.…”
Section: Discussionmentioning
confidence: 93%
“…Wang 21 also found that an abnormal ABI was more prevalent in patients with non-healing ulcers. High risk was also more prevalent among diabetics with reduced palpability of lower limb pulses (14.04%); correlating with Margolis, in whose study of diabetic foot patients, 20% had distal vasculopathy.…”
Section: Discussionmentioning
confidence: 93%
“…The MW system seems to correlate with the prognosis of diabetic foot ulcers (18), while the stages in the UT system were found to be helpful to predict amputation (11). In contrast to other classification systems such as the S(AD)SAD (16) and the PEDIS (perfusion, extent, depth, infection and sensation) (4), the MW and the UT systems do not assess ulcer site, degree of polyneuropathy or surface area.…”
Section: Discussionmentioning
confidence: 94%
“…Other results from clinical investigations included serum albumin (8/42), serum haemoglobin (7/42), glycaemic control (eg, HAb1C) (7/42), and renal function (eg, estimated glomerular filtration rate) (5/42). Only two studies investigated microbiology clinical investigations …”
Section: Resultsmentioning
confidence: 99%